The creativity conundrum - HENG, Andrew (Institutional Knowledge at Singapore Management University, 2024)
1. My survey of Chinese and German workers shows that the impact of remote work on creativity varies by gender, culture, and age. 2. Chinese women, in particular, grapple with cultural and gender norms that hamper creativity in remote work settings. 3. Hybrid work models can provide flexibility without sacrificing talent or creativity.